Factors Associated with Symptoms of Dermatitis in Prisoners in Class II A Jambi Penitentiary in 2024 - Andy Amir; Aisyah Rahmadiah; Fajrina Hidayati; Guspianto; Fitria Eka Putri (PT. Banjarese Pacific Indonesia, 2024)
The national prevalence of dermatitis in Indonesia based on Basic Health Research data by the Ministry of Health 2018 is 6.8% and tends to increase every year. Data from the Jambi Provincial Health Service, in 2021 dermatitis was ranked eighth with the most common disease with a percentage of 5.03%, while in 2022 it experienced an increase and was ranked sixth with a percentage of 5.96%. This study aims to determine the factors associated with symptoms of dermatitis in prisoners at the Class IIA Jambi Penitentiary in 2024. This research is a quantitative study using a cross sectional study design. The sampling technique used Proportionate Random Sampling on 1124 prisoners at the Class IIA Jambi Penitentiary by conducting interviews. Prisoners' knowledge was in the good category as much as 40.4% of respondents. Attitudes in the positive category were 37.2% of respondents. Prisoners with housing that meets the requirements are 21.3% of respondents. Bathing habits were in the good category as many as 53.2% of respondents. Clothing cleanliness was in the good category as many as 37.2% of respondents. Towel cleanliness was in the good category as many as 41.5% of respondents.